Coordinated control scheme of a hybrid renewable power system based on hydrogen energy storage. (November 2021) - Li, Zheng; Dong, Hao; Hou, Shaodong; Cheng, Liyuan; Sun, Hexu
Abstract: An all-weather energy management scheme for island DC microgrid based on hydrogen energy storage is proposed. A dynamic model of a large-scale wind–solar hybrid hydrogen-generation power generation system was established, using a quasi-proportional resonance (QPR). We used the distributed Nautilus vertical axis wind power generation system as the main output of the system, and it used the photovoltaic and hydrogen energy storage systems as alternative energy sources. Based on meeting the load power requirements and controlling the bus voltage stability, we can convert the excess energy of the microgrid to hydrogen energy. With a shortage of load power, we can convert the stored hydrogen into electrical energy for the load. Based on the ANSYS FLUENT software platform, the feasibility and superiority over large-scale distributed Nautilus vertical axis wind power generation systems are verified. Through the MATLAB/Simulink software platform, the effectiveness of the energy management method is verified. The results show that the large-scale distributed Nautilus vertical axis wind power generation system runs well in the energy system, produces stable torque, produces energy better than other types of wind turbines, and has less impact on the power grid. The energy management method can ensure the normal operation of the system 24 h a day under the premise of maintaining the stable operation of the electric hydrogen system without providing external energy.